Environmentally degradable starch filled low density polyethylene active packaging materials - Abu Bakar, Aznizam (Faculty of Chemical and Natural Resource Engineering, 2009)
Fibre reinforced polymer composites have many applications as a class of structural materials because of their ease of fabrication, relatively low cost and superior mechanical properties compared to polymer resins. Pineapple peel fibres (PAPF) have good potential as reinforcement in thermoplastic composite. It is the objective of the current research to develop a new formulation of PAPF biodegradable reinforced high density polyethylene as the material. Both HDPE and PAPF were compounded using extruder machine and then prepared for tensile test (ASTM D638), flexural test (ASTM D790) and impact test (ASTM D256) by using injection moulding machine. The PAPF/HDPE composites were characterized using Melt Flow Index (MFI), Scanning Electron Microscopy (SEM) and Fourier Transform Infra-Red (FTIR). MFI values of PAPF/HDPE composites decreased as the content of PAPF increased. SEM analysis clarified that the structure of 30 wt % PAPF/HDPE has fewer voids introduced by fibre pull out. FTIR results showed that O-H peak become broader with the increment of the fibre loading. As the PAPF loading in HDPE increased in term of wt%, the Young’s Modulus increased with fibre loading at the beginning and experienced optimum raise at 30 wt % of fibre loading. Conversely, it is found that the tensile strength declined as the fibre concentration in composite increased. It was also observed that the flexural modulus and strength of PAPF reinforced HDPE composite increased linearly with increment of fibre loadings. This trend was different for impact strength where it decreased as the fibre loading increased. The study concluded that the optimum fibre loading for the best performance of the composite is at 30 wt% fibre loading.